Pengaruh Disiplin Kerja, Motivasi dan Lingkungan Kerja terhadap Kepuasan Kerja Karyawan Yayasan Airlangga Balikpapan - Misna Ariani; Imam arrywibowo; Maulyani Mansur (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study employs a quantitative descriptive method to analyze the impact of work discipline, motivation, and work environment on employee job satisfaction at Yayasan Airlangga Balikpapan. The study population includes 135 employees, with a sample of 40 employees selected using quota sampling. Data collection was conducted through literature review, interviews, and Likert scale-based questionnaires. Data analysis utilized SMART PLS 04 to test the validity and reliability of instruments and hypothesis testing with Structural Equation Modeling (SEM). The results show that work discipline, motivation, and work environment significantly influence employee job satisfaction. The R-Square value of 0.752 indicates a good model, with job satisfaction influenced by 70.9% by work discipline, motivation, and work environment variables. Hypothesis testing reveals that work discipline, motivation, and work environment variables each have p-value < 0.05 and t-statistic > 1.96, thus accepting all hypotheses. In conclusion, work discipline, motivation, and work environment play crucial roles in enhancing job satisfaction. It is recommended to strengthen employee communication, improve adherence to regulations, and include other variables such as competence and leadership in future research.